A model of the effective dimensions of interactive learning systems for adults - Thomas C. Reeves; Patricia M. Reeves (Adult Education Research Conference, 1996)
Little agreement exists concerning the effective dimensions of interactive learning systems (ILS), including computer-based training, interactive multimedia, and the World Wide Web. This paper presents a model of interactive learning derived from research and theory in instructional technology and adult education. The model encompasses ten dimensions of interactive learning for adults, including 1) underlying psychology, 2) educational philosophy, 3) task orientation, 4) accessibility, 5) source of motivation, 6) instructor role, 7) metacognitive support, 8) interaction control, 9) cultural sensitivity, and 10) collaborative learning. Relationships among these ten dimensions and the principles of adult learning theory are explained, and recommendations for how these dimensions can be used for the design, implementation, and evaluation of ILS are made.